Pharmaceutical Carrier’s for Topical Drug Delivery System - D, Prasanthi; Usharani, Sagarla; Bhashpitha, Naredla (Asian Journal of Pharmaceutical Research and Development, 2023)
Beginning with a revenue breakdown of this specific market, this study seeks to describe the intricate world of drug carriers. A quick introduction of various different types of traditional and cutting-edge drug carrier systems is provided in the section that follows.Avariety of topical active substances, such as sunscreen ingredients, corticosteroids, and antibacterial, antifungal, and antiviral agents, can be delivered via foam technology. Ointments are semisolids used for external skin or mucous membrane treatment. Less than 20% of them often contain water and volatiles. Targeted medication delivery to and through the skin has a lot of potential using nano systems like micro emulsions and nano emulsions. By lowering surface and inter facial tension and increasing the viscosity of the aqueous phase, nanoemulgel improves a stable nano emulsion formulation. The various carrier types that the authors used in their formulation and conclusion have been added as a final effort for this work, highlighting the need to establish a strong double link between the newly developed industrial processes and the flexibility of medication delivery systems that is so desperately neededfor use with people.